Penanaman Perilaku Hidup Sehat Melalui Pembelajaran Sastra sebagai Upaya Pencegahan Wabah Covid-19 di Masa Adaptasi Kebiasaan Baru - Zoni Sulaiman; Asep Nurjamin; Lina Siti Nurwahidah; Ari Kartini; Nur Alyani Salsabila (Jurnal Pekemas, 2020)
The essence of learning literature in schools is as a vehicle for inculcating values ​​and refining the attitudes and minds of students as members of society. The formation of individual character and attitudes can be instilled in the community through the teaching of literature in the education sector. Thus the teaching of literature in schools must be delivered with contextual content and fun methods. This service is carried out with the aim of providing an understanding for SMP and MTS teachers in order to understand contextual and fun literary lessons so that they can be used to overcome problems that occur in the community. The problem that is currently being faced by the world community is preventing the spread of the Covid-19 outbreak. This service is expected to help the government in instilling healthy living behaviors for the community through literature learning in schools. The results of this dedication show that teachers can easily develop literary teaching materials in the form of poetry texts, anecdotal texts and short stories, which are charged with inculcating healthy living behaviors for students. The benefit of this research is the composition of teaching materials that are contextual and in accordance with the demands of the curriculum and are useful for social life in society.